Solve the system if equations by substitution

Y=3x-13
3x+2y=19

Answers

Answer 1
Answer: \left \{ {{y=3x-13} \atop {3x+2y=19}} \right. \n\nSubstitution\n\n3x+2(3x-13)=19\n\n3x+6x-26=19\n\n9x-26=19\ \ \ |add\ 26\n\n9x=45\ \ \ | divide\ by\ 9\n\nx=5\ny=3x-13=3*5-13=15-13=2\n\n\nx=5\ny=2
Answer 2
Answer:

The solution to the system of equations is x = 5 and y = 2.

Given that:

The system of equations:

y = 3x - 13                                   (1)

3x + 2y = 19                                 (2)

Step 1: Solve equation (1) for Y:

y = 3x - 13

Step 2: Substitute y from equation (1) into equation (2):

3x + 2(3x - 13) = 19

Step 3: Simplify the equation and solve for x:

3x + 6x - 26 = 19

9x - 26 = 19

9x = 19 + 26

9x = 45

x = 45/9

x = 5

Step 4: Substitute x = 5 into equation (1) to find Y:

y = 3(5) - 13

y = 15 - 13

y = 2

So, the values of x and y are 5 and 2, respectively.

Learn more about Equation here:

brainly.com/question/29657992

#SPJ6


Related Questions

Need help with 7,8,9,10 please help me
What property is shown in the equation?  –53 ÷ 1 = –53   A. division into zero property   B. identity property of division   C. negative one property of division   D. reciprocal property What property is shown in the equation? 5ac = 5ca   A. Identity Property of Multiplication   B. Reciprocal Property of Multiplication   C. Zero Property of Multiplication   D. Commutative Property of Multiplication
Need help with this question plz
Jon has to pay $7.50 admission for the skating rink and $1.50 per hour to rent rollerblades. Write an equation for the cost (y) based on the number of hours(x).
Jack is at a shop and sees than 5 antiques cost $10.he need 30 antiques cost

Find the product of 2x2(6x + 3). 12x3 12x3 + 3 12x3 + 6x2 2x2 + 6x + 3

Answers

Answer:

(option C/3) 12^3 + 6x^2

Step-by-step explanation:

Took test, got it right. Idk how, cause I was stump to.

Answer:

C.  12x³ + 6x²

Step-by-step explanation:

I'm an FLVS kid and got the question right, so I wanted to explain my answer:

You just have to use the distributive property for this one. Multiply 2x² by each term in the brackets.

2x²(6x + 3) ← original question for ref.

2x²(6x) = 12x³

  • 2 · 6 = 12
  • x² · x = x³
  • ("x" techniqually has a placeholder exponent of 1. To multiply two exponents with the same base, you just add the exponents. So x2 + x1 = x3.)

2x²(3) = 6x²

  • 2 · 3 = 6
  • Keep the variable and exponent the same

So the new terms are 12x³ +  6x²

The answer is C.

Which digit is in the hundredths place?
579.246

Answers

The hundredths place is located two places to the right of the decimal point. Therefore, the digit 4 is in the hundredths place. Hope this helps! :)

The city planning committee is composed of 12 women and l4 menWhat fraction of the committee is composed of men?

Answers

to solve you must dive 14 by 12 then simplify to the nearsest tenth.


the answer is 6/13!!!!!! have a great day!!!!!!!

Joe has a collection of 35 DVD movies. He received 8 of them as gifts. Joe bought the rest of his movies over years. If bought the same number of movies each year ,how mamy movies did joe buy last year ?

Answers

Answer: Joe bought 27 DVDs movies last year.

Step-by-step explanation:

Since we have given that

Number of DVD movies Joe has a collection = 35

Number of DVDs as gifts out of them = 8

So, Rest of his movies over years is given by

35-8=27

According to question, if he bought the same number of movies each year.

Hence, Joe bought 27 DVDs movies last year.

Subtract 35-8=27 then take that and divide by how many years he's been buying movies and you have your answer

The length of a side of an equilateral triangle is x - 4.5. First express its perimeter as a sum. Next express its perimeter as a product. Explain why the two expressions are equivalent.

Answers

Equilateral triangle means all sides have equal length.
Perimeter
As a sum: (x-4.5)+(x-4.5)+(x-4.5)
As a product: 3 * (x-4.5)
They are equivalent because 3 times a number is just the sum of three of the number.

What is 10 5/16-(5 1/4 +2 9/16)

Answers

10(5)/(16)-(5(1)/(4)+2(9)/(16))=\ \ \ \ | make\ common\ denominator\n\n10(5)/(16)-(5(4)/(16)+2(9)/(16))=\ \ \ | omit\ the\ bracket\n\n10(5)/(16)-5(4)/(16)+2(9)/(16)=7(5-4+9)/(16)=7(10)/(16)\n\nSolution\ is\ 7(10)/(16).